Ethical and academic landscape of AI in Malaysian polytechnics - Muslimin, Mohamad Siri; Haidzir, Muhammad Hafidz; Mohd Noor, Marjan (Faculty of Accountancy, 2025)
There is no denying that artificial intelligence (AI) has become an influential force in education and beyond. The technological advancements are substantial, ranging from sophisticated algorithms capable of trend prediction to generative AI tools such as ChatGPT that can produce essays or code (Bhandari, 2023). The integration of emerging technologies aligns closely with national strategic priorities. The (Ministry of Education Malaysia., 2015), through Malaysia Education Blueprint 2015- 2025 (Higher Education) (MEB-HE), identified Leap 9, titled "Globalised Online Leaming," which emphasizes the use of technology to deliver flexible and globally accessible education. Although AI is not explicitly referenced in the original blueprint, its emphasis on digital learning provides a foundational pathway for the adoption of AI technologies.